Effect of Service Quality on the utilization of Puskesmas Penerokan Bajubang District Batanghari Regency - Andy Amir; Adila Solida; Arnild Augina Mekarisce; Nurmala Sari (CV. AFDIFAL MAJU BERKAH, 2022)
Utilization of Healt Center services in a region can be a reflection of public health status in the region. For 4 (four) consecutive years there was a significant decrease in the number of visits at the Panerokan Health Center, Batanghari Regency. This indicates a decrease in the quality of services at the Panerokan Health Center. This study aims to identify the influence of service quality with the utilization of Panerokan Health Center, Bajubang District, Batanghari Regency. Quantitative research using cross sectional design with a population of 1,549 people. Sample calculation using lemeshow formula, which is as many as 63 samples with accidental random sampling technique. The research instruments used questionnaire sheets, then the data were processed through data editing, data coding, data entry, data cleaning, and data processing, then analyzed univariate, bivariate with chi-square test, and multivariate with double logistic regression test. The results showed that 74.6% utilization of Healt Center included in the good category. There is a significant influence of reliability factor (p-value = 0.007), responsiveness factor (p-value = 0.003), assurance factor (p-value = 0.005), and empathy factor (p-value = 0.000) on the utilization of Healt Center Penrokan. The most dominant factor affecting the utilization of Penerokan Health Center is reliability (OR=0.023). there is the influence of reliability, responsiveness, assurance and empathy to the utilization of Panerokan Health Center. Reliability factor becomes the most dominant factor affecting the utilization of Healt Center. It is recommended that the Panerokan Healt Center conduct periodic evaluations related to the reliability of Healt Center employees in providing services that are in accordance with the provisions and increase responsibility and discipline during working hours.